COMPARATIVE ANALYSIS OF THE SIGNIFICANCE OF BLOOM'S TAXONOMY IN IELTS EXAMS (COMPARATIVE ANALYSIS OF LISTENING, READING, WRITING, SPEAKING) - Raimova Nigora; Ziyoda Saparbayeva; Zahiriddin Sadriddinov; Mehroj Ergashev; Doniyor Kamoldinov; Sunnatova Mohinur; Muattarxon Shuxratova; Muattarxon Shuxratova (Bright Mind Publishing, 2025)
In this article, we will explore the relationship between cognitive thinking and performance on the IELTS exam, with a particular focus on the application of Bloom's Taxonomy, a well-established framework for understanding different levels of cognitive engagement. By understanding the connection between cognitive thinking and IELTS performance, we can better understand the holistic nature of language assessment and provide valuable insights for both test-takers and educators.
Keywords: Assessment, IELTS, Bloom’s taxonomy, remember, understand, apply, analyze, evaluate, and create, cognitive thinking, english proficiency, fluency, coherence, cohesion, lexical resource.